2017
DOI: 10.1542/peds.2016-1758e
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Costs of Social Media in Adolescence

Abstract: In 2015, American adolescents aged 13 to 18 years reported using social media 1 hour and 11 minutes a day, 7 days a week. Social media are used for a variety of activities, including sharing information, interacting with peers, and developing a coherent identity. In this review of the research, we examine how social media are intertwined with adolescent development and assess both the costs and benefits of adolescent social media use. We include suggestions for further research and recommendations for clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 19 publications
5
166
0
5
Order By: Relevance
“…The growing presence of social media has prompted a proliferation of research across disciplines investigating its uses and effects among youth (Uhls et al 2017; Yan 2018). However, research on adolescent peer relationships has lacked a unifying framework for understanding the mechanisms by which social media may impact traditional peer relations constructs.…”
Section: Introductionmentioning
confidence: 99%
“…The growing presence of social media has prompted a proliferation of research across disciplines investigating its uses and effects among youth (Uhls et al 2017; Yan 2018). However, research on adolescent peer relationships has lacked a unifying framework for understanding the mechanisms by which social media may impact traditional peer relations constructs.…”
Section: Introductionmentioning
confidence: 99%
“…There are many benefits of social media use for individuals across the life span (Antheunis et al, 2016;Chopik, 2016;Heo et al, 2015;Steinfield et al, 2008;Uhls et al, 2017). For young people, the benefits include a variety of factors that are critical to healthy development, such as identity development and exploration, aspirational development, peer engagement, friendship development and maintenance, increased social capital, and access to social support (Uhls et al, 2017). One study of over 3,000 early adolescents showed a positive relationship between the use of social networking sites and quality of friendships (Antheunis et al, 2016).…”
Section: Benefits and Potential Harms Related To Social Media Usementioning
confidence: 99%
“…The literature presents an increasing number of documented negative consequences related to social media use (Ho et al, 2016;LeBourgeois et al, 2017;Lin et al, 2016;Pew Research Center, 2018;Primack et al, 2017;Uhls et al, 2017). Evidence suggests links between social media use and depression, anxiety, and social isolation (Lin et al, 2016;Primack et al, 2017).…”
Section: Benefits and Potential Harms Related To Social Media Usementioning
confidence: 99%
See 1 more Smart Citation
“…Five Working Groups specifically deliberate on psychosocial effects research. Uhls et al 4 address how social media influence identity development, aspirational development, and peer engagement for adolescents (ages 13-18 years). James et al 5 present the current state of knowledge on how digital lives of tweens and teenagers influence their sense of well-being, social connectedness, empathy, and narcissism.…”
Section: Psychosocial Effectsmentioning
confidence: 99%